Mathematics 2011 | Study Mode

Join Discuss Share to WhatsApp
Question 11
A
2X - 1
B
X + 3
C
2X + 1
D
X - 3
Explanation
X2 + 1 \(\frac{X - 2}{\sqrt{X^3 - 2X^2 + 3n - 3}}\)

= \(\frac {- 6X^3 + n}{-2X^2 + 2X - 3}\)

= \(\frac{(-2X^2 - 2)}{2X - 1}\)

Remainder is 2X - 1

Correct option: A
Join Discuss Share to WhatsApp
Question 12
A
(3y - 2x)(3y + 4x)
B
(3y + 4x)(3y + 4x)
C
(3y + 2x)(3y - 4x)
D
(3y - 4x)(3y + 4x)
Explanation
9y2 - 16x2

= 32y2 - 42x2

= (3y - 4x)(3y +4x)

Correct option: D
Join Discuss Share to WhatsApp
Question 13
A
-3, -9
B
9, -3
C
-9,3
D
3, -9
Explanation
-2x -5y = 3

x + 3y = 0

x = -3y

-2 (-3y) - 5y = -3

6y - 5y = 3

y = 3

but, x = -3y

x = -3(3)

x = -9

therefore, x = -9, y = 3

Correct option: C
Join Discuss Share to WhatsApp
Question 14
A
20\(\frac{1}{4}\)
B
27
C
2\(\frac{1}{4}\)
D
36
Explanation
x \(\alpha\sqrt y\)

x = k\(\sqrt y\)

81 = k\(\sqrt9\)

k = \(\frac{81}{3}\)

= 27

therefore, x = 27\(\sqrt y\)

y = 1\(\frac{7}{9}\) = \(\frac{16}{9}\)

x = 27 x \(\sqrt{\frac{16}{9}}\)

= 27 x \(\frac{4}{3}\)

dividing 27 by 3

= 9 x 4

= 36

Correct option: D
Join Discuss Share to WhatsApp
Question 15
A
\(\frac{1}{18}\)
B
\(\frac{1}{12}\)
C
\(\frac{1}{24}\)
D
\(\frac{1}{6}\)
Explanation
T \(\alpha \frac{1}{R^3}\)

T = \(\frac{k}{R^3}\)

k = TR3

= \(\frac{2}{81}\) x 33

= \(\frac{2}{81}\) x 27

dividing 81 by 27

k = \(\frac{2}{2}\)

therefore, T = \(\frac{2}{3}\) x \(\frac{1}{R^3}\)

When R = 2

T = \(\frac{2}{3}\) x \(\frac{1}{2^3}\) = \(\frac{2}{3}\) x \(\frac{1}{8}\)

= \(\frac{1}{12}\)

Correct option: B
Join Discuss Share to WhatsApp
Question 16
A
x \(\leq\) 2
B
x \(\geq\) -1
C
x \(\geq\) -2
D
x \(\leq\) -1
Explanation
-6(x + 3) \(\leq\) 4(x - 2)

-6(x +3) \(\leq\) 4(x - 2)

-6x -18 \(\leq\) 4x - 8

-18 + 8 \(\leq\) 4x +6x

-10x \(\leq\) 10x

10x \(\leq\) -10

x \(\leq\) 1

Correct option: B
Join Discuss Share to WhatsApp
Question 17
A
x < -3 or x > 5
B
-5 < x < 3
C
x < 3 or x > 5
D
x > 3 or x < -5
Explanation
x2 + 2x > 15

x2 + 2x - 15 > 0

(x2 + 5x) - (3x - 15) > 0

x(x + 5) - 3(x + 5) >0

(x - 3)(x + 5) > 0

therefore, x = 3 or -5

then x < -5 or x > 3

i.e. x< 3 or x < -5

Correct option: D
Join Discuss Share to WhatsApp
Question 18
A
505
B
513
C
433
D
635
Explanation
3, 6, 9,..., 36.

a = 3, d = 3, i = 36, n = 18

Sn = \(\frac{n}{2}\) [2a + (n - 1)d

S18 = \(\frac{18}{2}\) [2 x 3 + (18 - 1)3]

= 9[6 + (17 x 3)]

= 9 [6 + 51] = 9(57)

= 513

Correct option: B
Join Discuss Share to WhatsApp
Question 19
A
60
B
62
C
54
D
64
Explanation
T2 = 4, T4 = 16

Tx = arn-1

T2 = ar2-1 = 4 i.e. ar3 = 16, i.e. ar = 4

T4 = ar4-1

therefore, \(\frac{T_4}{T_r}\) = \(\frac{ar^3}{ar}\) = \(\frac{16}{4}\)

r2 = 4 and r = 2

but ar = 4

a = \(\frac{4}{r}\) = \(\frac{4}{2}\)

a = 2

Sn = \(\frac{a(r^n - 1)}{r - 1}\)

S5 = \(\frac{2(2^5 - 1)}{2 - 1}\)

= \(\frac{2(32 - 1)}{2 - 1}\)

= 2(31)

= 62

Correct option: B
Join Discuss Share to WhatsApp
Question 20
A
- \(\frac{1}{2}\)
B
\(\frac{1}{3}\)
C
-1
D
2
Explanation
N + Y = XY + X + Y

3 + -\(\frac{2}{3}\) = 3(- \(\frac{2}{3}\)) + 3 + (- \(\frac{2}{3}\))

= -2 + 3 -\(\frac{2}{3}\)

= \(\frac{1 - 2}{1 - 3}\)

= \(\frac{1}{3}\)

Correct option: B

Try this quiz in in E-test/CBT Mode
switch to Mathematics 2011 in CBT Mode

Previous Page Next Page
Question Map
Quiz link
Share Mathematics 2011 with your audience
Share to WhatsApp CBT mode Study mode copy link
​​​Help keep QUIZZERWEB running! 
A donation makes a contribution towards the costs, the time and effort that's going on in building and improving this platform.